You can't! The daily exercise of police authority in Rio de Janeiro : 1907-1930 - Bretas, Marcos Luiz (1995)
The police of Rio de Janeiro had an important role in the reform of the city in the early twentieth century. The impetus to build a modem city influenced elite intellectuals to try to reform the police in the modem, scientific fashion. After the first wave of reforms receded, the police was abandoned to a less prominent role, and left without resources to carryon the modernising process, resulting in the need to develop their own methods of work derived from their daily experience. The main purpose of this thesis is to look closely at daily police activity, trying to show how policemen developed their ways of viewing the world and their procedures from the experiences they faced. From their contacts with state administrators, in the figure of the Chief of Police, with members of the elite. and with the vast majority of poor citizens, policemen began to define the extent and limits of their power, building their place in the networks of patronage and authority that permeated Rio's society. They had to combine an unchecked power to deal with those they classified as the criminal classes, composed of the dispossessed, and an attitude of subservience to the powerful, in a pattern that characterises twentieth-century policing in Rio de Janeiro